2019
DOI: 10.1002/aoc.5052
|View full text |Cite
|
Sign up to set email alerts
|

Post modification of zinc based coordination polymer to prepare Zn‐Mo‐ICP nanoparticles as efficient self‐supported catalyst for olefin epoxidation

Abstract: Preparation, characterization, and catalytic properties of bimetallic coordination polymer constructed from 2‐aminoterephthalic acid as linker, zinc cations as node, and cis‐dioxo molybdenum units as catalytic active sites are reported via two pathways. Molybdenum centers were placed in N,O positions created by condensation reaction of 2‐aminoterephthalic acid with salicylaldehyde while zinc cations coordinated via carboxylic acid groups of linker to achieve infinite chains of metalo‐ligand. The obtained coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…For investigating the nature of active species involved in the photocatalytic degradation experiments, trapping tests were conducted, in which Ru-Zn-ICP was employed as the photocatalyst for RhB degradation upon visible light irradiation, and the results are given in Figure b. Three scavengers, i.e., isopropyl alcohol (IPA), ethylenediaminetetraacetic acid (EDTA), and benzoquinone (BQ), were utilized for identifying • OH, photogenerated h + , and • O 2 – , respectively, which are the main active species involved in photocatalytic degradation processes . The results showed that utilizing IPA as a scavenger results in decreasing RhB degradation in comparison to the conditions performed in the absence of scavenger, indicating a little involvement of • OH species in the degradation process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For investigating the nature of active species involved in the photocatalytic degradation experiments, trapping tests were conducted, in which Ru-Zn-ICP was employed as the photocatalyst for RhB degradation upon visible light irradiation, and the results are given in Figure b. Three scavengers, i.e., isopropyl alcohol (IPA), ethylenediaminetetraacetic acid (EDTA), and benzoquinone (BQ), were utilized for identifying • OH, photogenerated h + , and • O 2 – , respectively, which are the main active species involved in photocatalytic degradation processes . The results showed that utilizing IPA as a scavenger results in decreasing RhB degradation in comparison to the conditions performed in the absence of scavenger, indicating a little involvement of • OH species in the degradation process.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the product was separated and rinsed with methanol five times through centrifugation–redispersion cycles. The obtained Zn-ICP solid was dried under vacuum for 24 h …”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] Therefore, using a solid material to heterogenize the molybdenum Schiff-base complexes seems more applicable in many aspects especially for facile separation of catalyst. Several solid materials including activated carbon, [5] carbon nanotube, [6] graphene oxide, [7] chitosan, [8] SBA-16, [9] magnetite nanoparticles, [10] coordination polymers [11] and metal organic frameworks [12] have been utilized to heterogenize molybdenum Schiff-base complexes on the surface or within the pores.…”
Section: Introductionmentioning
confidence: 99%